Academically Gifted & Albino: A Narrative Study of a Twice-Exceptional - Sengil Akar, Seyma; Akar, İbrahim (Pen Academic Publishing, 2020)
This research focuses on the educational and daily life of a gifted individual with albinism. The purpose of this current research was to determine the difficulties faced by this twice-exceptional individual in his education life and how these difficulties have been overcome. The study has been conducted by narrative study design of the qualitative method. Research data were collected through semi-structured interviews conducted with the individual himself, his mother and one of his friend. Data analyses revealed four different themes, such as: difficulties due to visual impairment and strategies to cope with these difficulties, difficulties experienced due to physical disadvantages and ways of overcoming them, being gifted and socio-emotional difficulties. More specifically, the twice-exceptional individual, who has visual impairment due to albinism (90%), continued his formal education throughout the whole education life without attending inclusion classes, and encountered many difficulties specific to those who see little, such as having difficulty in following the course and course notes. In addition to these, the twice-exceptional individual is an unrecognized gifted student (academically) who exhibited early development in the childhood period and who has achieved outstanding academic success at undergraduate and postgraduate level after having been in the 0.01% portion among the students taking the university entrance exam. As gifted, he has not received any special support in the education system. It is seen that the support of his family throughout his education life is an effective factor playing an important role in the shaping of the education life of the twice-exceptional individual, who has been confronted with many social-psychological difficulties because his difference from others as a gifted individual with albinism.
Keywords: 4. Education; 10. No inequality